Prevalence and influence factor of drug-related problems in inpatients with kidney disease: a prospective single central study - Guoguang Gu; Yanping Li; Yunyun Hu; Hengyi Zhao; Xingdong Wang; Xiaomin Li; Xinran Zhang; Hong Zhu; Xiaohua Dai; Xingxing Liu; Liyan Miao; Jianguo Zhu; et al. (Frontiers in Pharmacology, 2024)
AimsTo investigate the prevalence and influencing factors of drug-related problems (DRPs) in inpatients with kidney disease to provide reference data for pharmaceutical care.MethodsThe basic information, diagnoses, and medication reconciliation (MR) of inpatients in the Department of Nephrology at our hospital between October 2020 and September 2021 were collected. The Chinese-modified DRP version based on the PCNE classification (Version 9.1) was used to assess, intervene and statistically analyze the results of the patients’ DRPs. The influence factor of DRPs in inpatients with kidney disease was analyzed by the multivariate binary logistic regression.ResultsOf 623 patients included in this study, 132 (21.80%) had DRPs. The prevalence of anemia was significantly higher in patients with DRPs than those without DRPs (43.18% vs. 28.72%, p < 0.05), the mean number of drug types consumed (7.25 ± 3.44 with DRPs vs. 5.93 ± 3.58 without DRPs, p < 0.05) and the proportion of ≥5 drugs (%) (79.55% with DRPs vs 58.04% without DRPs, p < 0.05) were significantly increased. In addition, the prevalence of hypertension (76.52% vs. 68.64%), diabetes (27.27% vs. 22.20%) and hyperuricemia (16.67% vs. 13.65%) in DRP patients were higher than those without DRPs, but there was no statistical difference (p > 0.05). The logistic regression analysis showed that patients with anemia (OR = 1.702, 95%CI: 1.146–2.529, p = 0.008), average number of medication types taken (OR = 1.089, 95%CI: 1.034–1.147, p = 0.001) significantly increased the risk of DRPs. The distribution of harm levels was as follows: 78 problems (59.09%) were level C, 29 (21.97%) were level B, 10 (7.58%) were level D, 7 (5.30%) were level A, 7 (5.30%) were level E, and 1 (0.76%) were level F. All DRPs were resolved after 128 interventions.ConclusionRenal anemia, the average number of drug varieties consumed, and the proportion of ≥5 drugs are associated with the occurrence of DRPs. Pharmacists conducting MR services can reduce DRPs of inpatients in the department of nephrology and ensure patient drug safety.